Learning in the museum - Hein, George E. (London ; New York : Routledge, 1998)
The significance of museum education -- Educational theory -- Early visitor studies -- The countenance of visitor studies -- Ladder and network theories -- Studying visitors -- Evidence for learning in the museum -- The Constructivist Museum.
CCS Gent
boek